Population pharmacokinetics and pharmacodynamics of lumefantrine in young Ugandan children treated with artemether-lumefantrine for uncomplicated malaria - Tchaparian, E; Sambol, N; Arinaitwe, E; McCormack, S; Bigira, V; Wanzira, H; Muhindo, M; Creek, D; Sukumar, N; Blessborn, D; Tappero, J; Kakuru, A; et al. (Oxford University Press, 2016)
The pharmacokinetics and pharmacodynamics of lumefantrine, a component of the most widely used treatment for malaria, artemether-lumefantrine, has not been adequately characterized in young children.Capillary whole-blood lumefantrine concentration and treatment outcomes were determined in 105 Ugandan children, ages 6 months to 2 years, who were treated for 249 episodes of Plasmodium falciparum malaria with artemether-lumefantrine.Population pharmacokinetics for lumefantrine used a 2-compartment open model with first-order absorption. Age had a significant positive correlation with bioavailability in a model that included allometric scaling. Children not receiving trimethoprim-sulfamethoxazole with capillary whole blood concentrations <200 ng/mL had a 3-fold higher hazard of 28-day recurrent parasitemia, compared with those with concentrations >200 ng/mL (P = .0007). However, for children receiving trimethoprim-sulfamethoxazole, the risk of recurrent parasitemia did not differ significantly on the basis of this threshold. Day 3 concentrations were a stronger predictor of 28-day recurrence than day 7 concentrations.We demonstrate that age, in addition to weight, is a determinant of lumefantrine exposure, and in the absence of trimethoprim-sulfamethoxazole, lumefantrine exposure is a determinant of recurrent parasitemia. Exposure levels in children aged 6 months to 2 years was generally lower than levels published for older children and adults. Further refinement of artemether-lumefantrine dosing to improve exposure in infants and very young children may be warranted.